Candida under the lens: species diversity and antifungal susceptibility trends - Pandey, Nidhi; Paul, Pradeep; Das, Parijat; Tilak, Ragini (International Journal of Research in Medical Sciences, 2026)
Background: Non-albicans Candida (NAC) species are increasingly responsible for mucosal and invasive candidiasis and often exhibit reduced susceptibility to antifungal agents. This study assessed the species distribution of clinical Candida isolates and their antifungal susceptibility profiles. Methods: In a prospective study conducted from 2015 to 2018 at a tertiary care center in Varanasi, India, 711 Candida isolates obtained from blood, urine, aspirates, and mucosal swabs were analyzed. Species identification was performed using PCR-restriction fragment length polymorphism (PCR-RFLP); unresolved isolates were further characterized by MALDI-TOF mass spectrometry and sequencing. Results: Antifungal susceptibility to fluconazole, voriconazole, caspofungin, and amphotericin B was determined using the CLSI broth microdilution method. NAC species accounted for 63% of isolates, with Candida tropicalis being the most prevalent. PCR-RFLP identified 92.5% of isolates, while MALDI-TOF MS and sequencing enabled identification of rare species, including C. mesorugosa, C. africana, and Pichia farinosa. Fluconazole showed high activity against C. albicans (94.3%) and C. glabrata (100%) but reduced activity against C. tropicalis (77.9%). Voriconazole demonstrated broad activity across species, and caspofungin exhibited low MICs for most isolates, although resistance was observed in 10.6% of C. glabrata. Amphotericin B remained active against most species, with elevated MICs noted in C. lusitaniae. Conclusions: These findings underscore the importance of accurate species-level identification and routine antifungal susceptibility testing to optimize therapy for Candida infections.